FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MP-ASI DINI PADA BAYI DI WILAYAH KERJA PUSKESMAS BASUKI RAHMAT KOTA BENGKULU - Suryani Suryani; S. Effendi; Nurmaya Pebrianti (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
The impact if complementary foods was given early is the infants will become more easily sick, ranging from cough, colds, fever, constipation, or diarrhea. The purpose of this study was to study the factors associated with early complementary feeding practices of infants in working area of Basuki Rahmat Public Health Center Bengkulu. This research used Cross Sectional design. The population of this study was all mothers who had infants aged 7-12 months, amounting to 328 mothers. The sampling technique used Simple Random Sampling technique which amounted to 77 mothers. Data collection in this study used primary and secondary data with statistical test Chi-Square (χ2) through SPSS program. The results of this study were from 77 mothers of infants aged 7-12 months, 51 mothers (66.2%) had good knowledge, 51 mothers (66.2%) had a pre-prosperous social economy, 44 mothers (57.1%) did not work, 59 mothers (76.6%) gave complementary food age 6 months. There was no significant relationship between mother's knowledge, mother's work status, and social economy with early complementary feeding practices in working area of Basuki Rahmat Public Health Center Bengkulu. It was expected that Basuki Rahmad Public Health Center to do counseling about exclusive breastfeeding and complementary feeding practices to pregnant women and mothers who have children under five in working area of Basuki Rahmat Public Health Center Bengkulu. Keywords : complementary food, employment status, knowledge, social economic